An introduction to mechanical engineering - Wickert, Jonathan A. (Cengage Learning, 2012)
AN INTRODUCTION TO MECHANICAL ENGINEERING introduces students to the ever-emerging field of mechanical engineering, giving an appreciation for how engineers design the hardware that builds and improves societies all around the world. Intended for students in their first or second year of a typical college or university program in mechanical engineering or a closely related field, the text balances the treatments of technical problem-solving skills, design, engineering analysis, and modern technology.